2003
DOI: 10.1080/02786820300970
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Particle Size Distribution Estimation from Digital Image Analysis

Abstract: One of the most serious problems associated with Diesel engines is pollutant emissions, specially nitrogen oxides and particulate matter. However, although current emissions standards in Europe and America with regard to light vehicles and heavy duty engines refer to the particulate limit in mass units, there has been increasing concern of late to know the size and number of particles emitted by engines. This interest has been promoted by the latest studies about the harmful effects of particles on health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 20 publications
2
43
0
4
Order By: Relevance
“…Several studies proposed nucleation mode limits between 30 and 50 nm [23]. In this study, nucleation mode particles was decomposed from 5.6 to 30 nm.…”
Section: Transient Soot Measurement Through Three Different Techniquesmentioning
confidence: 99%
“…Several studies proposed nucleation mode limits between 30 and 50 nm [23]. In this study, nucleation mode particles was decomposed from 5.6 to 30 nm.…”
Section: Transient Soot Measurement Through Three Different Techniquesmentioning
confidence: 99%
“…When mass PM is analysed in Figure 16 (after converting particle number into particle mass emissions through the particle density correlation proposed in Lapuerta et al 36 ), two main differences can be observed with respect to particle number emissions, regardless of the fuel used:…”
Section: Particle Emissionsmentioning
confidence: 99%
“…Values for a log-normal distribution with r o = 0.234 µm and σ = 1.5 were taken from Lapuerta et al (2003), and N o was assumed to be the same as that for sulfate aerosol, i.e., 8.3 × 10 6 particles/m 3 . …”
Section: Soot Aerosolsmentioning
confidence: 99%